Problems of Over-abundant Populations of 'Nilgai' and 'Blackbuck' in Haryana and Madhya Pradesh and their Management - Chauhan, N. P. S.; Sawarkar, V. B. (Indian Forester, 1989)
Wildlife damage problems are as old as man, but have come into focus as a management issue for reasons of some species adapting themselves to the changing environs and thriving in the man altered habitats. Consequently, there is a clash with interests of local people. Crop raiding by locally over-abundant wild herbivores is one such problem. The paper analyses the crop raiding problem by nilgai in Haryana and by blackbuck in the Karera G.I.B. Sanctuary, M.P. and seeks to offer management strategies to minimize the problem.